Integration of Thematic Interpretation and Physiology of Prayer Movements: An Interdisciplinary Study of Surah Al-Tin and Musculoskeletal Balance - Lusi Ismayenti (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: Prayer, as a fundamental act of worship in Islam, not only has spiritual value but also contains physiological dimensions that have the potential to improve musculoskeletal health. The urgency of this research lies in the need for an interdisciplinary approach that integrates thematic interpretation of the Qur'an with physiological science to understand the relationship between the spiritual dimension and human body balance. This article aims to examine the relationship between the concept of "ahsani taqwīm" in Surah Al-Tīn and the musculoskeletal balance mechanism reflected in prayer movements. Methodology: This research uses a qualitative method with a thematic interpretation approach (maudhu'i) and literature study of classical and contemporary literature on physiology, biomechanics, and interpretation. Results: The results of this study indicate that prayer movements such as bowing, prostrating, and sitting between two prostrations involve the activation of key muscles that play a role in maintaining posture and balance. The integration of the theological meaning of taqwīm and the physiology of movement demonstrates that prayer is a form of worship that is in harmony with the human anatomical system and has the potential to be a preventative therapy for musculoskeletal disorders. This research contributes to strengthening the paradigm of embodied spirituality that connects science and Islamic theology.. Applications/Originality/Value: ValueThis research contributes to strengthening the embodied spirituality paradigm that connects science and Islamic theology. In conclusion, prayer can be understood not only as an expression of faith but also as a bodily balance mechanism that reflects the perfection of human creation. Further research is recommended to test these findings through an empirical approach based on biomechanical measurements.